A Glimpse Sight of Balinese Millennials Worker: Work-Life Balance – Culture Perspective - Pradnyawati, Ni Putu Manik Indah; Eunhye, Seong; Pidada, Ida Ayu Iswari (Universitas Pendidikan Nasional, 2024)
The research is conducted by Qualitative method which aims to identify the importance of work-life balance to millennial moms and also investigate the impact of work from home on the work-life balance of millennial moms. Working from home has now become a habit for Indonesian people, including in Bali, carried out by various generations including millennial women in Bali. Based on the phenomenon of this research the author researches Denpasar, Bali. The object of this research is millennial moms work who experience working from home at a regionally owned enterprise. The phenomenology approach by Creswell is used. The result shows almost all of the dimensions in work from home refer to millennial moms' work-life balance, based on interview results, the dimensions of work interference with personal life, personal life interference with work are related to a flexible work environment, stress disorders, and separation of home and office work, while personal life enhancement of work is related to health and balance and work enhancement of personal life related to high creativity and productivity. The mileage does not pose a problem because the informant is located in Denpasar and is close to the office area. Local regulations that affect the millennial moms' work-life balance in the previous study were not found in the current study. Time management takes part in maintaining the work-life balance of millennial moms when work from home exists. The novelty of the current research is focuses on the millennial mom's generation.